Biodiesel Synthesis of Cotton Seeds Oil (Ceibapentandra) By Chemically Transesterification Process and Ion Fragmentation of Methyl Ester - Erin Ryantin Gunawan; Siska Ayu Wulandari; Emmy Yuanita; Dedy Suhendra (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Fossil fuel is commercial energy sources in many communities where their abundance progressively reduced and the resulting environmental pollution. Biodiesel is one alternative fuel made from vegetable which oils are suitable to replace the function of fossil fuels and environmentally friendly. Synthesis of biodiesel from cotton seeds oil was carried out by chemically ransesterification process. Composition of methyl esters in biodiesel thatwas analyzed by GC-MS are methyl palmitate (16.71%), methyl 8,11-octadecadienoic (46.45 %) and methyl linoleate (4.21 %).The highest amount of biodiesel conversion isat ratio of oil and methanol (1:1) with the catalyst 1% (weight of oil). The produced biodiesel was 93.7 %. Chemical properties of the produced biodiesel meets the standard SNI 04-7182-2006 i.e. saponification value of 120.167 mg KOH / g, acid value of 0.28 mg KOH / g and iod value 55.84g iod/100g of sample.